Penerapan Konseling Individu dengan Teknik Self Management untuk meningkatkan Motivasi belajar bagi sisawa korban brokenhome di MTs NU Terate Gresik - Fitriyani, Arindah (JURNAL ISLAMIKA, 2023)
Incomplete families have a big influence on the emergence of juvenile delinquency, the phenomenon of divorce is increasingly common so it has a big impact on children's behavior. The aim of this research is to help increase learning motivation in students who are victims of Broken Home by using Self Management Techniques. The methods used are observation and interviews. Findings in the field and literature studies show that some students whose families are separated tend to have low motivation to learn. This is confirmed through interviews with guidance and counseling teachers and also the homeroom teacher. These students often cause trouble in class and outside of class. Using the right techniques will help students to increase their motivation to learn in order to become successful people in the future. After the researchers conducted counseling using the Self Management Technique, it could be concluded that this technique was suitable for students with learning motivation problems, and after completing this counseling, students showed changes in behavior that were initially negative to positive.